Factors Affecting Willingness to Pay for National Health Insurance Program among Informal Workers in Indonesia - Aji, Budi; Masfiah, Siti; Harwanti, Siti; Ulfah, Nur (JURNAL INFO KESEHATAN, 2023)
The effort to achieve universal health coverage for all people under a single-payer national health insurance in Indonesia still experiences a substantial challenge particularly related to informal workers. This population faces a number of challenges, including income irregularity, a lack of educational variety, the fact that the majority of workers live in rural areas, and a lack of health insurance literacy. The objective of this study was to examine the factors that influence informal workers' willingness to pay for a national health insurance program in Indonesia. This cross-sectional study was conducted in the Banyumas district of Central Java, Indonesia. Employing a multistage random sampling technique, 316 workers in the informal sector were recruited as study participants. Logistic regression was employed to investigate the factors that influence willingness to pay for national health insurance premiums. According to the study findings, urban, national health insurance information, and uneducated factors were related to informal workers' willingness to pay for national health insurance. Workers who lived in urban area (p < 0.05, OR = 3.922) were more willing to pay for insurance premium. Workers who received better exposure of national health insurance information (p < 0.05, OR = 2.330) were more willing to pay for premium. Furthermore, workers who uneducated (p < 0.05, OR = 14.847) were more willing to pay for premium. The national health insurance campaign serves as a catalyst for increasing public awareness of this program. Adequate and widespread national health insurance program information dissemination would aid in the effectiveness of Indonesia's efforts to achieve the goal of universal health insurance coverage.